2017
DOI: 10.1021/acs.analchem.7b02568
|View full text |Cite
|
Sign up to set email alerts
|

Ion Source with Laser Triangulation for Ambient Mass Spectrometry of Nonplanar Samples

Abstract: The analysis of nonplanar samples in ambient mass spectrometry poses a formidable challenge. Here, an ion source equipped with laser triangulation for analyzing nonplanar surfaces was constructed. It was designed as a two-position device, where the sample height was measured using laser triangulation and the target compounds were then analyzed. Thanks to a stage movable in xyz, the ion source maintained an optimal vertical distance between the sample and the sampling capillary for each measured spot during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Laser-based MSI methods are affected by the sample surface topology, but it is possible to compensate the roughness of plant surfaces for improving the lateral resolution by either laser triangulation , or profilometry …”
Section: Discussionmentioning
confidence: 99%
“…Laser-based MSI methods are affected by the sample surface topology, but it is possible to compensate the roughness of plant surfaces for improving the lateral resolution by either laser triangulation , or profilometry …”
Section: Discussionmentioning
confidence: 99%
“…Technical refinements of spray-based ambient ionization MS techniques have been recently pursued to improve their analytical reproducibility. DESI performance, in particular, is dependent on source and geometrical optimization, with slight alterations in source parameters greatly affecting ion signal intensity. , To address source irreproducibility, Tillner et al showed that positioning of the solvent capillary within the outer gas capillary in the DESI sprayer was a major contributor to spray-to-spray variability . By increasing the outer diameter of the spray capillary and using a positioning disk within the DESI source (left panel, Figure ), the relative standard deviation (RSD) was reduced by a factor of 9.1 within individual sprayers and by a factor of 9.7 across sprayers when compared to the commercial source .…”
Section: Development Of Ambient Ionization Techniquesmentioning
confidence: 99%
“…However, it is very sensitive to matrix effects, which can significantly affect the observed spatial distribution of analytes. In particular, physical properties (roughness on the surface of the analysed sample) can profoundly affect the analysis and the reliability of results obtained using this method [72][73][74]. Rejšek et al [74] recently showed that DESI-MS can also be applied to non-planar samples by using an ion source with a laser triangulation system.…”
Section: Ms Ambient Techniquesmentioning
confidence: 99%